New chinglish in social media: Chinese college students’ language usage patterns - Liu Xiaoman; Esther Jawing; Zhao Xiaofang (Global Academic Excellence (M) Sdn Bhd, 2023)
The large number of English learners in China establishes a strong foundation for English users in the country. The rapid development of Chinese social media platforms offers a broader platform for English usage in China. College students, with their bilingual or multilingual backgrounds, play a vital role in using English. Unlike the traditional English taught in educational settings, English used on social media differs and is referred to as New Chinglish. This study aims to explore the role of New Chinglish in the lives of college students on Chinese social media platforms, focusing on their behaviours and habits related to its usage. The qualitative analysis findings highlight the commonality of using New Chinglish among college students, often evolving into an unconscious habit. Moreover, New Chinglish has transcended the confines of the social media platform, extending into offline life. The study also reveals contradictory emotional trends underlying their user behaviour and habits. It provides a detailed description of the role of New Chinglish in the lives of Chinese youth, emphasizing the integration of English as a part of their daily routines. Additionally, this study contributes significantly to the existing literature by depicting the English usage situation in China.